The importance of clusters for the development of small & medium enterprises - Garcia, Roberto Barriga (2009)
This thesis aims to open a theoretical discussion on the importance of cluster for the development of Small and Medium Enterprises. The methodology applied was based on bibliographical and qualitative research. The basic questions raised by this study can be summarized as follows: How the creation of a cluster will help in the development of the SME?. Consequently, the final objective of the work is to identify which are the characteristics that help into the success of a Small & Medium Enterprises inserted in a cluster. The answer to this question led the research to a better understanding of (i) the characterization of the Small & Medium Enterprises; (ii) the clusters theory; (iii) evidence for a developed (Italy) and a developing (Chile) country that support our proposition to verify. The main results confirm the relevance of the cluster for the development of the Small and Medium Enterprises because of the collective efficiency that generates, improving the funding conditions, the exporter capacity and diminishing the activities costs of the small companies that are part of the conglomerate.